Moisture Adsorption Behavior in Anodes for Li‐Ion Batteries. Issue 2 (17th May 2019) - Eser, Jochen C.; Wirsching, Tobias; Weidler, Peter G.; Altvater, Andreas; Börnhorst, Tobias; Kumberg, Jana; Schöne, Gerrit; Müller, Marcus; Scharfer, Philip; Schabel, Wilhelm
Abstract : Excessive moisture adsorbed in electrodes and separators of a Li‐ion battery hampers its performance and is, therefore, removed to a certain amount in a post‐drying process. An insufficient understanding of the process results thereby in high process costs. Cost reductions can only be achieved efficiently with an improved process understanding by modeling this post‐drying process. As process modeling requires knowledge of sorption equilibria of water in the components of the battery, the sorption equilibria of water in different anodes are determined by means of a magnetic suspension balance and compared with different experimental setups. The measured data of the adsorption isotherms are described mathematically and give an impression of the amount of moisture, which is going to adjust at an equilibrium starting from a dry anode. Moreover, the materials of the anode are evaluated for their moisture sorption behavior. It is shown that mass‐weighted sorption equilibria of water in the materials yield a good approximation of equivalent equilibria in the anode. In the investigated anodes, the binder and rheology additive carboxymethyl cellulose (CMC) accounts for the most water uptake. Abstract : Sorption equilibria of moisture in components of lithium‐ion batteries are an important fundament for an improved understanding of the post‐drying process, which has hardly been scientifically investigated. Therefore, adsorption equilibria of moisture in anodes with different material compositions and structures are presented. Furthermore, the contribution of the equilibria of the individual materials to the equilibrium of the anode is investigated.